2019
DOI: 10.2147/cmar.s208984
|View full text |Cite
|
Sign up to set email alerts
|

<p>Secreted TGF-beta-induced protein promotes aggressive progression in bladder cancer cells</p>

Abstract: Background: Transforming growth factor-beta-induced (TGFBI) is an exocrine protein, which has been found to be able to promote the development of nasopharyngeal carcinoma, glioma, pancreatic cancer, and other tumors. However, there is currently no report concerning the relationship between TGFBI and invasive progression of bladder cancer (BCa). Methods: IHC staining, qRT-PCR and Western blot were used to analyze TGFBI and EMT markers levels. In vivo tumorigenesis was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…Although the molecular background responsible for the high expression of TGFBI in high-grade UC remains elusive, our in vitro results obtained in 5637 cells demonstrate that TGFBI clearly holds an independent and, most likely, unfavorable role in the progression of UC. Our results are corroborated by Zou and colleagues who, very recently, proved a significantly increased level of TGFBI mRNA and protein in the tissues of patients with muscle invasive bladder cancers and showed that a high TGFBI tissue expression was correlated with the histological grade and clinical stage [41].…”
Section: Discussionsupporting
confidence: 87%
“…Although the molecular background responsible for the high expression of TGFBI in high-grade UC remains elusive, our in vitro results obtained in 5637 cells demonstrate that TGFBI clearly holds an independent and, most likely, unfavorable role in the progression of UC. Our results are corroborated by Zou and colleagues who, very recently, proved a significantly increased level of TGFBI mRNA and protein in the tissues of patients with muscle invasive bladder cancers and showed that a high TGFBI tissue expression was correlated with the histological grade and clinical stage [41].…”
Section: Discussionsupporting
confidence: 87%
“…TGFBI is secreted by bladder cancer cells to induce proliferation, migration, and invasion, as well as EMT in an autocrine manner. Moreover, TGFBI overexpression stimulates the growth of bladder cancer xenografts in mice [206]. Interestingly, enhanced TGF-β1 expression was suggested as a mechanism mediating cancerous effects of chronic long-term low-dose ionizing radiation exposure [207].…”
Section: Bladder Cancermentioning
confidence: 99%
“…Some researchers 44,45 have demonstrated the linkage between DPYSL2 and mTOR signaling pathway, and the activation of mTOR signaling pathway is crucial for T cell differentiation 46 , suggesting the potential function of DPYSL2 in immunobiology of bladder cancer. TFGBI is an exocrine protein and could promote the malignant phenotypes of BLCA 47,48 . Recent study 49 has identi ed TGFBI as an immune-relevant biomarker for prognosis of clear cell renal cell carcinoma based on multiple datasets, verifying our interesting ndings.…”
Section: Discussionmentioning
confidence: 99%